2000
DOI: 10.1590/s0104-66322000000400007
|View full text |Cite
|
Sign up to set email alerts
|

Control and optimization of baths for electrodeposition of Co-Mo-B amorphous alloys

Abstract: Optimization and control of an electrodeposition process for depositing boron-containing amorphous metallic layer of cobalt-molybdenum alloy onto a cathode from an electrolytic bath having cobalt sulfate, sodium molybdate, boron phosphate, sodium citrate, 1-dodecylsulfate-Na, ammonium sulfate and ammonia or sulfuric acid for pH adjustments has been studied. Detailed studies on bath composition, pH, temperature, mechanical agitation and cathode current density have led to optimum conditions for obtaining satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
10
0
3
Order By: Relevance
“…They have argued that NaH 2 PO 2 acts as an accelerator that changes the kinetics of Co and Mo codeposition . Prasad et al have claimed that Co–Mo–B coatings obtained from citrate based baths are found to have interesting properties such as high hardness, corrosion resistance, wear resistance and also sufficient ductility . Balaraju et al have obtained Ni–W–P alloy coatings by electroless deposition and found that ternary Ni–W–P deposits have shown higher hardness values compared to binary Ni–W deposits .…”
Section: Introductionmentioning
confidence: 99%
“…They have argued that NaH 2 PO 2 acts as an accelerator that changes the kinetics of Co and Mo codeposition . Prasad et al have claimed that Co–Mo–B coatings obtained from citrate based baths are found to have interesting properties such as high hardness, corrosion resistance, wear resistance and also sufficient ductility . Balaraju et al have obtained Ni–W–P alloy coatings by electroless deposition and found that ternary Ni–W–P deposits have shown higher hardness values compared to binary Ni–W deposits .…”
Section: Introductionmentioning
confidence: 99%
“…O objetivo principal da MSR é determinar as condições ótimas de operação para um sistema ou determinar uma região que satisfaça as especificações operacionais 13 . Para dar continuidade aos trabalhos que estão sendo desenvolvidos no Laboratório de Eletroquímica e Eletroanalítica da Universidade Federal de Campina Grande [14][15][16][17] , este trabalho deu ênfase ao processo de otimização do banho eletrolítico para eletrodeposição da liga de Fe-W-B em função da sua eficiência de deposição e resistência à corrosão . Foi usada a metodologia de superfície de resposta para auxiliar no processo de otimização.…”
Section: Introductionunclassified
“…But no experimental difficulty is experienced in codepositing tungsten with the group 8 metals. Several authors have investigated the process of electrodeposition of tungsten with iron group metals in aqueous solutions [2][3][4][5][6]. It is well known that alloys such as Co-W-B and Ni-W-B are characterized by high surface hardness; Vickers hardness values between 450 and 650 kgf mm )2 have been reported for these coatings in the as-deposited condition [6][7][8].…”
Section: Introductionmentioning
confidence: 99%